Role of epidermal primary cilia in the homeostasis of skin and hair follicles - Croyle, Mandy J. (Company of Biologists, 2011)
Skin and hair follicle morphogenesis and homeostasis require the integration of multiple signaling pathways, including Hedgehog (Hh) and Wingless (Wnt), and oriented cell divisions, all of which have been associated with primary cilia. Although studies have shown that disrupting dermal cilia causes follicular arrest and attenuated Hh signaling, little is known about the role of epidermal cilia. Here, epidermal cilia function was analyzed using conditional alleles of the ciliogenic genes Ift88 and Kif3a. At birth, epidermal cilia mutants appeared normal, but developed basaloid hyperplasia and ingrowths into the dermis of the ventrum with age. In addition, follicles in the tail were disorganized and had excess sebaceous gland lobules. Epidermal cilia mutants displayed fewer long-term label-retaining cells, suggesting altered stem cell homeostasis. Abnormal proliferation and differentiation were evident from lineage-tracing studies and showed an expansion of follicular cells into the interfollicular epidermis, as is seen during wound repair. These phenotypes were not associated with changes in canonical Wnt activity or oriented cell division. However, nuclear accumulation of the ΔNp63 transcription factor, which is involved in stratification, keratinocyte differentiation and wound repair, was increased, whereas the Hh pathway was repressed. Intriguingly, the phenotypes were not typical of those associated with loss of Hh signaling but exhibited similarities with those of mice in which ΔNp63 is overexpressed in the epidermis. Collectively, these data indicate that epidermal primary cilia may function in stress responses and epidermal homeostasis involving pathways other than those typically associated with primary cilia.